Profile of Science Literacy Competence of Junior High School Students in Ecology and Biodiversity in Indonesia - Syahida Ainaya; Winny Liliawati; Lilit Rusyati (UIN Fatmawati Sukarno Bengkulu, 2025)
The importance of science literacy skills prompted this study to analyze the profile of science literacy competence of junior high school students in biodiversity in Indonesia. OECD defines science literacy as the ability to identify questions, acquire new knowledge, explain scientific phenomena, and draw conclusions based on facts. This research uses a quantitative approach involving 200 students from SMP Negeri 1 Pagaden Subang and SMPN 2 Pagaden Subang. The E-Test consisted of 25 questions distributed via WhatsApp Group by natural science subject teachers. Data were processed using Microsoft Excel and grouped based on the difficulty level of the questions (low, medium, high). The results show that junior high school students' science literacy skills are still in the low category. In explaining scientific phenomena competence, the percentage of correct answers for low and medium difficulty questions reached 66% and 67%, respectively, while for high difficulty questions it was only 55%. In evaluating and designing scientific investigations competence, questions with low difficulty levels had the highest percentage of correct answers (68%), followed by medium (56%) and high difficulty levels (43%). In interpreting scientific data and evidence competence, questions with low difficulty levels reached 78%, medium 69%, and high 58%. These findings are consistent with previous studies showing the low science literacy of students in various regions of Indonesia. Therefore, more intensive and sustainable efforts are needed to improve students' science literacy through more effective and interactive learning methods and teacher training. The results of this study are expected to serve as a reference for policymakers in formulating more appropriate education strategies to improve students' science literacy competence in Indonesia.